Moderately Hydrophobic Polymer Protective Layer Enables Zn (100) Deposition for High Utilization Zinc Anodes - Fan, Xiaoming; Wu, Peiyi; Jiao, Yucong (Nano-Micro Letters, 2026)
Evolving Zn anodes with high areal capacity at elevated depths of discharge (DOD) is crucial for scalable aqueous battery, yet plagued by dendritic growth and parasitic reactions. Here, we constructed a polymer protective layer (PDMAG@Zn) comprising hydrophobic poly(N,N-dimethylacrylamide) (PDMAA) and zincophilic cationic guar gum (CGG) via an in situ strategy. The moderately hydrophobic property of PDMAA prevents the "Grotthuss" effect on Zn surface to inhibit parasitic reactions while synergistically accelerates Zn2+ desolvation behavior with a molecular lubrication mechanism. Additionally, the PDMAG layer guides Zn2+ deposition along (100) plane for rapid stripping/plating performance. Coupled with CGG-induced interfacial stabilization, the symmetrical batteries achieve ultralong cycling of 6580 h at 1 mA cm−2, 1 mAh cm−2, and 300 h at 1 mA cm−2, 15 mAh cm−2 with 91.5% DODWeight. Furthermore, the Zn||V2O5 full battery delivers a high capacity of 335 mAh g−1 at 1 A g−1, underscoring superior feasibility in practical applications. Highlights: 1 The moderately hydrophobic property of polymer protective layer (PDMAG) prevents the "Grotthuss" effect on Zn surface to inhibit hydrogen evolution reaction. 2 The PDMAG protective layer guides Zn2+ deposition along (100) plane for rapid stripping/plating. 3 PDMAG enables efficient Zn utilization under high DODWeight for aqueous zinc ion batteries.